THE INSALUBRITY CAUSED BY HOUSEHOLD WASTE IN THE CITY OF BUKAVU AND ITS IMPACT ON THE AQUATIC FAUNA ECOSYSTEM OF LAKE KIVU : « CASE OF THE COMMUNE OF KADUTU ». - Joseph MWEZE SEBUMBA,; Pr Dr Christ Hermann POUNAH,; Valery MUHAYA NTAMUSIMWA,; Justin MUTARUSHWA KATEMBERA,; Marie Salomé MAWAZO SEBUMBA., (IJRDO - Journal of Social Science and Humanities Research, 2025)
This study aims to assess the problem of poor housedhold wastemanagement and its environmental risks in the Bukavu city, specificallywithin the Kadutu area. Among other things, it aims to assess the causes ofpoor household waste management. We used direct observation anddocumentary analysis methods that allowed us to collect data in the fieldthrough surveys. We have reached the results that weak involvement ofstate authorities, anafchic constructions, the non-involvement of sanitationagents, the incivility of the population, rural exodus, pirate markets,morals, customs and habits constitute the root caused of the poormanagement of insalubrity caused by househoid waste in the city ofBukavu and particularly in the commune of Kadutu. Most of theinhabitants who have their homes all along the rivers « Kahuwa and Nyakishe » do not have garbage cans, they dump their waste, and all typesof garbage in these rivers. This results in the destruction of ecosystem andaquatic fauna of Lake Kivu, which leads to a decline in the fishreproduction cycle and pollution of the waters of Lake Kivu.These harmful and visible effects are at the root of several epidemic,waterborne diseases in the City of Bukavu and more particularly in thesaid municipality and cause harmful consequences on the health of thepopulation, on the ecosystem and the aquatic fauna of Lake Kivu.